2017
DOI: 10.1021/acsami.7b10511
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon Nanotubes Dramatically Affect the Fruit Metabolome of Exposed Tomato Plants

Abstract: Here, we reported that multiwalled carbon nanotubes (MWCNT) added to hydroponics system can enhance fruit production of exposed tomato plants. We quantified the exact amount of MWCNT accumulated inside of fruits collected by MWCNT-exposed plants using an advanced microwave induced heating technique (MIH). We found that absorption of MWCNT by tomato fruits significantly affected total fruit metabolome as was confirmed by LC-MS. Our data highlight the importance of comprehensive toxicological risk assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Despite this increasing concern, CNTs effects on plant morpho logical, physiological, and molecular processes and their mecha nisms of action are far from being fully understood (Line et al 2017;Verma et al, 2019). It has been reported several times that exposure to CNTs can lead to an enhancement of plant productivity in both hydroponic medium (McGehee et al, 2017;Pandey et al, 2018;Lahiani et al, 2018) and soil conditions Pandey et al, 2019). However, other studies have shown that CNTs can lead to phytotoxic effects: decreased plant growth, increased generation of reactive oxygen species or decreased cell dry weight (Hao et al, 2018;Wang et al, 2017;Lin et al, 2009).…”
Section: Plant Materials and Cultivationmentioning
confidence: 99%
“…Despite this increasing concern, CNTs effects on plant morpho logical, physiological, and molecular processes and their mecha nisms of action are far from being fully understood (Line et al 2017;Verma et al, 2019). It has been reported several times that exposure to CNTs can lead to an enhancement of plant productivity in both hydroponic medium (McGehee et al, 2017;Pandey et al, 2018;Lahiani et al, 2018) and soil conditions Pandey et al, 2019). However, other studies have shown that CNTs can lead to phytotoxic effects: decreased plant growth, increased generation of reactive oxygen species or decreased cell dry weight (Hao et al, 2018;Wang et al, 2017;Lin et al, 2009).…”
Section: Plant Materials and Cultivationmentioning
confidence: 99%
“…Furthermore, NPs loaded with the chemical active ingredients have also extended the scope of microsurgery in plants through triggered release 7 10 . To understand the physiological consequences 11 14 , a comparison of the vascular uptake of NPs was carried out. Interestingly, some aquatic plants showed greater uptake of NPs than ions 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that carbon-based nanomaterials (CBNs) cover around 40% of all engineered nanomaterials used for agricultural applications 6 . To date, the interactions of CBNs with plant systems have been studied in different plant organs including seeds, seedlings, plants, and plant cell cultures 617 . Positive effects of CBNs on seed germination and plant productivity have been documented for model plant species 8,11–13 , food crops (corn, barley, soybean) 14 as well as for bioenergy crops (sorghum, switchgrass) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of CBNs on seed germination and plant productivity have been documented for model plant species 8,11–13 , food crops (corn, barley, soybean) 14 as well as for bioenergy crops (sorghum, switchgrass) 15 . One of the most promising discoveries is the ability of a wide range of CBNs to induce early flower development and significantly stimulate the production of flowers and fruits of plants grown in hydroponics or soil supplemented with CBNs 16,17 . This discovery may lead to the establishment of highly efficient technology with a focus on the improvement of commercially important crops such as flower producing species (ornamental plants) or/and fiber producing plants (cotton).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation